(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
NexusSafe is a real-time malicious URL detection system designed to enhance web security using Explainable Artificial Intelligence (XAI). The system integrates a browser-based Chrome Extension with a FastAPI backend to monitor and analyze URLs visited by users. It employs a multi- layered detection approach that includes lexical feature analysis, infrastructure evaluation, behavioral inspection, and threat intelligence integration using external platforms. Unlike traditional blacklist-based systems, which fail to detect newly generated malicious URLs, NexusSafe uses intelligent techniques to identify both known and unknown threats effectively. Additionally, the system generates human-readable explanations for each prediction, allowing users to understand the reasons behind classifying a URL as safe or malicious. This combination of real-time detection, accuracy, and transparency makes NexusSafe a reliable and user-friendly solution for modern cybersecurity challenges